Septic tendonitis of the deep digital flexor tendon in a Thoroughbred horse referred for weight loss and intermittent fever. (19th December 2015) - Santinelli, I.; Beccati, F.; Passamonti, F.; Pepe, M.
Summary: This case report describes the history, clinical and diagnostic findings, treatment and outcome of a 3‐year‐old Thoroughbred gelding. The horse was examined for chronic weight loss, intermittent fever of 4 months' duration and acute lameness of 2 weeks' duration, and was finally diagnosed with septic tendonitis of the deep digital flexor tendon and digital flexor tendon sheath caused by Streptococcus equi ssp. zooepidemicus . Investigation of the lower respiratory tract also allowed isolation of S. equi ssp. zooepidemicus . Although surgical treatment was recommended, because of the severity of the lesion and the guarded prognosis for a return to full athletic function, the owner declined surgery. The horse was therefore treated aggressively with antimicrobials using systemic, local and regional approaches, and with anti‐inflammatory drugs. At 20 months after discharge, the horse was able to race, and he is now in full work with 20 races finished successfully.